República, política e direito : representações do trabalho docente e a trajetória de Carvalho Neto (1918-1921) - Lima, Maria do Socorro (2008)
This study have by objective to analisys the representations of the teaching work, culturals praticals and the production place of the passage has by the intellectual of education Antônio Manoel de Carvalho Neto, identifying in this context, the configuration of the educational disposal at that period. The methodology of this investigation is a biographic boarding. Carvalho Neto was General Director of Public Instruction, President of Superior Advice of Education, and Director of Normal School between 1918-1920. After of the experience at Direction of the Public Instruction, defended a Project to creation of classrooms and school adjusted to Abnormal Children, has teachers of the Sergipe Commerce School Orlando Council Member , and it crowned its insertion in the educational field as the first Director of the Law school of Sergipe, in 1951. In the General Direction of Instruction has emphasis to Scholar Inspection Service. The orientation of this study is supported in the teoric-methologic contributions of the New History and Cultural History. In the History of the Education, the investigation of the trajectory of Carvalho Neto it allowed to understand significants aspects of the teaching work´s configurations in the first half of the century XX in Sergipe.